Perbandingan Algoritma Sequitur dan RLE Dalam Kompresi Teks - Rian Syahputra (Graha Mitra Edukasi, 2022)
Information on a news blog is not small if we look at the amount of information that will be conveyed in a news story. A news blog also uses a lot of storage memory in the database because of the large amount of information in the form of text that is stored, and also affects the speed of data transmission. Compression techniques aimed at reducing data can be used to reduce stored text and save storage media and speed up the data transmission process. Using the Sequitur algorithm is better with a compression ratio of 80.95% of the initial size, because the sequitur algorithm removes symbol pairs that appear more than once with a new symbol. While the RLE algorithm in this study cannot be used because it does not meet the RLE algorithm so that the compression process does not occur due to the absence of the same characters appearing successively, this is a weakness of the RLE algorithm